Evaluation of Human Leukocyte Aantigens in Papillon Lefevre Syndrome - SH Fargadian; B Gharesi Fard; M Lotf Azar (Tehran University of Medical Sciences, 2003)
Papillon Lefevre Syndrome (PLS) is a rare disease, associated with the early onsetperiodontal break down in deciduous and permanent dentition.The etiology of PLS is not exactly determined but recently, mutation in catespin C gene, as a genetic basis for the disease, has been established. The aim of this study was to investigate the HLA status in patients affected with PLS. In this research, the frequency of HLA-I and HLA-DR in 9 PLS patients (Belonged to seven unrelated families) were compared with 37 healthy people (controls). Fisher exact test was used for data analysis. The results indicated that the frequency of HLA-B18 was significantly higher in the patients' group, compared to the control group(P<0.05). The present study, based on the serological methods, is the only existing controlled study regarding PLS. However, in order to get accurate results, a molecular technology with more samples is required.